The hello, goodbye window - Juster, Norton, 1929-2021. ([New York, NY] : Hyperion Books for Children, 2005)
A little girl describes the magic kitchen window in her grandparents' home.
"Michael de Capua Books"--T.p.
Caldecott Medal (2006); Boston Globe-Horn Book Honors: Picture Book (2005).
Keywords: Grandparent and child -- Juvenile fiction; Grandparents -- Juvenile fiction; Windows -- Juvenile fiction; Day -- Juvenile fiction; Grandparent and child -- Fiction; Grandparents -- Fiction; Windows -- Fiction; Caldecott Medal; Day -- Fiction; Picture books for children -- Juvenile fiction